AFGHAN-TAJIK DEPRESSION: ARCHITECTURE OF SEDIMENTARY COVER AND EVOLUTION - Nikolaev V.G. (My University, 2002)
Discussed is a singular Cenozoic feature, the Afghan-Tajik depression, spanning areas located in Tajikistan, Afghanistan, and Uzbekistan. The study draws on CMP profiling (regional and prospect scale), drilling, and other geological and geophysical evidence, and also a wealth of published data. Most of the data, especially seismics, are published for the first time. Structural maps showing depth to various horizons of sedimentary cover and depth to the inferred crystalline basement have been constructed. Structural mismatch exists between subsalt strata and the overlying molasse assemblage. Subsalt structural features are more equant and gentle. The molasse assemblage is dominated by various types of folds, including isoclinal, accompanied by overthrusts and nappes. Formerly, the folds were believed to converge in the Garm valley region on the north and to diverge southward. This concept is an artifact of overmuch focusing on the area north of the Pyandzh River (i.e., the Former USSR territory), while ignoring the structure of the Afghan territory. While considering the entire Afghan-Tajik depression, primarily its Cenozoic portion, one finds that Alpine-type folds of the molasse assemblage make a westward convex arc. This arc begins near Garm and terminates approximately at the level of the Alburz-Mormul EW-trending fault. On the north and south, the depression is bounded by the Dushanbe and north Afghan benches, elevated above the depression's interior and modified by equant highs and basins. The arcuate arrangement of Cenozoic folds suggests that their origin was related to detachment along the top of salt strata. This detachment may have been due to the westward pressure from the Pamir block against an empty space, because the average height of the Pamir block is ca. 4 km, and the surface of sediments of the Afghan-Tajik depression has elevations between 0 and 100-200 m. Consequently, folding was controlled by lateral compression due to expansion of crystalline rock mass, and not by crustal blocks moving in one or another direction.
Keywords: AFGHAN--TAJIK DEPRESSION; SEDIMENTARY COVER AND EVOLUTION; CENOZOIC; Cenozoic; Кайнозой